2019
DOI: 10.5530/ijpcs.2019.8.11
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist's Awareness and Knowledge of Reporting Adverse Drug Reactions in Saudi Arabia

Abstract: Objectives: Pharmacovigilance is considered a useful tool in detecting, assessing, understanding and preventing Adverse drug reactions (ADRs) to ensure the safety of medications and protect consumers from ADRs. Consequently, the progression and expansion of pharmacovigilance is urgent for safe and effective clinical practice; therefore, in this study, we aimed to compare the awareness and knowledge of the community and hospital pharmacists toward reporting ADRs in different regions of Saudi Arabia. Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
(24 reference statements)
0
3
1
Order By: Relevance
“…In contrast to studies conducted in Al Riyadh and Ash Sharqiyah, our study shows that community pharmacists have high awareness and knowledge regarding pharmacovigilance and methods of reporting ADRs (Bawazir, 2006;Khan, 2013;Mahmoud et al, 2014;AlRuthia et al, 2018;Al Doughan et al, 2019). Most of the respondents had 5-10 years of working experience with a full-time contract and had served more than 100 patients/customers daily.…”
Section: Discussioncontrasting
confidence: 85%
“…In contrast to studies conducted in Al Riyadh and Ash Sharqiyah, our study shows that community pharmacists have high awareness and knowledge regarding pharmacovigilance and methods of reporting ADRs (Bawazir, 2006;Khan, 2013;Mahmoud et al, 2014;AlRuthia et al, 2018;Al Doughan et al, 2019). Most of the respondents had 5-10 years of working experience with a full-time contract and had served more than 100 patients/customers daily.…”
Section: Discussioncontrasting
confidence: 85%
“…During an emergency, providing quality information within a stipulated time could be life-saving (Al Doughan, Alomi, & Iflaifel, 2019). Still, the pre-rotation survey revealed that 84% of the student pharmacists felt they could respond at their own pace.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of the educational intervention in improving the mean knowledge score of pharmacists about ADRs underscores the importance of providing explicit education to pharmacists about ADRs at both undergraduate and practice level. Topics related to pharmacovigilance are not given due share in the curricula offered by the majority of institutions offering medicine, pharmacy or nursing programmes in Saudi Arabia [7]. This could be explained by the lack of availability of enough qualified staff trained in pharmacovigilance and medication safety in Saudi Arabia [6].…”
Section: Discussionmentioning
confidence: 99%
“…The under-reporting of ADRs could be partly attributed to the lack of awareness and understanding of ADRs by healthcare professionals in Saudi Arabia. A cross-sectional study conducted to assess the knowledge of pharmacists about ADRs in Saudi Arabia reported inadequate knowledge and understanding about pharmacovigilance [7]. More than half of the participants of the study, including pharmacists, doctors and nurses, were not even aware of the correct definition of pharmacovigilance.…”
Section: Introductionmentioning
confidence: 99%